Produção de onze variedades de gramíneas para capineiras, em Viçosa, MG: Resultados preliminares - Zúñiga, M P; Sykes, D J; Gomide, J A (Revista Ceres, 2025)
In an experiment conducted at UREMG, 11 species and varieties of tropical forage grasses are being evaluated for -potential productivity and response to fertilizers. Stage of cutting was based on the phenology of the grass, usually at the seed-emergence stage. Yields in green forage per cutting, during the 1964-65 summer season varied from 7 metric tons/ha for Axonopus scoparius to 78 metric tons/ha for Porto Rico 534, a variety of Pennisetum purpureum. Setaria sphacelata, a species new to this region and having desirable vegetative characteristics, yielded 40 tons of green forage per hectare.